An estimated two-country EA-US model with limited exchange rate pass-through - Gregory De Walque; Philippe Jeanfils; Thomas Lejeune; Yuliya Rychalovska; Rafael Wouters (National Bank of Belgium, 2017)
We develop a two-country New Keynesian model with sticky local currency pricing,distribution costs and a demand elasticity increasing with the relative price. These features help to reduce the exchange rate pass-through to import price at the border and down the chain towards consumption price, both in the short and the long run. Oil and imported goods enter at the same time as inputs in the production process and as consumption components. The model is estimated using Bayesian full information maximum likelihood techniques and based on real and nominal macroeconomic series for the euro area and the United States together with the bilateral exchange rate and oil prices. The estimated model is shown to perform well in an out-of-sample forecasting exercise and is able to reproduce most of the cross-series co-variances observed in the data. It is then used for forecast error variance decomposition and historical decomposition exercises.
Keywords: C11; E32; E37; F41; 330; Open-economy macroeconomics; DSGE models; exchange-rate pass through; Bayesianinference; forecasting; policy analysis